Who Is Destroying Life on the Planet? the Confrontation of the Anthropocene and Capitalocene Concepts in the Environmental Debate [¿Quién Está Destruyendo la Vida en el Planeta? la Confrontación de Los Conceptos Antropoceno y Capitaloceno en el Debate ambiental1 - Estenssoro-Saavedra, J (Universidad de Talca, 2021)
The paper is inscribed in studies of the ideas and theoretical-political dimension of the environmental debate, understanding by this debate all the discussion relative to overcoming the global environmental crisis. In this regard, it hypothesizes that the criticism that the Capitalocene concept realizes to the Anthropocene concept, would tend to stimulate the theoretical political debate about the global environmental crisis, which involves answering questions such as what and who would be responsible for it, when did it begin, how is it overcome, resituating the debate in one of the most important theoretical-political debates of modernity, such as the capitalism-anti-capitalism tension. For these effects, the central theses of both concepts are exposed, which seek to answer the questions posed in order to highlight their theoretical confrontation. © 2021 Universidad de Talca. All rights reserved.